Phlebology, Vein Surgery and Ultrasonography Diagnosis and Management of Venous Disease - Mowatt-Larssen, Eric.; Desai, Sapan S.; Dua, Anahita; Shortell, Cynthia E. K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The management of venous pathology has been revolutionized by technological advancements. Venous disease is now managed with a wide variety of techniques that collectively allow physicians to diagnose and treat venous problems in ways that few surgeons would have anticipated even a decade ago. Techniques include laser ablation, radiofrequency ablation, chemical ablation (sclerotherapy), high ligation with or without stripping, ambulatory phlebectomy, powered phlebectomy, subfascial endoscopic perforator surgery, three-dimensional venography, and intravascular ultrasound. All of these topics are covered in this comprehensive, up-to-date textbook, which guides the practitioner through every aspect of care of the venous patient and includes essential background information on anatomy and pathophysiology. This book is exceptional in that it is based entirely on the curriculum designed for board certification by the American College of Phlebology (ACP). A further unique aspect of the text is the integration of ultrasound and various other imaging modalities, that play a fundamental role in diagnosis and management. The authors come from a wide range of specialties, mirroring the diversity of practitioners who care for patients with venous disease. The book will accordingly serve the needs of vascular and general surgeons, interventional radiologists, phlebologists, nurses, ultrasonographers, allied health professionals, and scientists, as well as American College of Phlebology fellowship candidates and those preparing for board examinations in vascular surgery.
Basic Sciences: Anatomy -- Pathophysiology of Reflux.-Presentation of Chronic Venous Disease.-Reflux Management. Vein Testing: Ultrasound Physics.-Ultrasound For Reflux.-Ultrasound For Phlebology Procedures.-Physiologic Testing -- Conventional and Cross-Sectional Venography. Superficial Vein Therapy -- Endovenous Thermal Ablation -- Chemical Superficial Vein Ablation -- Surgical Techniques -- Transcutaneous Laser Vein Ablation. Non-Superficial Veins: Perforator Veins -- Upper Deep Vein Disease -- Lower Deep Vein Disease -- Low Flow Vascular Malformations. Thrombosis: Ultrasound for Thrombosis -- Superficial Venous Thrombophlebitis -- Deep Vein Thrombosis -- Anticoagulation for Venous Thromboembolism -- Thrombophilias. Special Topics: Lymphedema -- Venous Leg Ulcers -- Biostatistics -- Vein Anesthesia.
Keywords: Medicine; Surgery; Vascular Surgery; Medicine & Public Health; Surgery; Vascular Surgery